Effect of Diabetes and Pre-Diabetes and its associated risk factors on treatment outcome of TB patients attending Government Hospitals in Haldwani of District Nainital, Uttarakhand - Saurabh Shukla; CMS Rawat; R.G Nautiyal (International Journal of Health and Clinical Research, 2021)
Background: Diabetes mellitus has the potential to fuel the epidemic of tuberculosis (TB). The world seems to face a looming co-epidemic of TB-diabetes, and that this is a serious public health issue we need to address urgently. DM may have a negative impact on the outcome of TB treatment: higher failure rates, higher rates of all-cause mortality, and death specifically related to TB. Methods: This study is a hospital based prospective study carried out in Government Medical College & Dr. Sushila Tiwari Government Hospital and S.S.J Base hospital, Haldwani, District Nainital of Uttarakhand. 400 tuberculosis patients who were registered to DOTS center of Government Medical College, Haldwani and S. S. J. Base Hospital, Haldwani in the third quarter (July to September) of the year 2015 were included in the study by Systematic random sampling. Results: The mean age of the study participants was 37.8±15.9 years. Hypertension and smoking were associated with unsuccessful treatment outcome. It was seen that Diabetic patients were significantly associated with unsuccessful treatment outcome (38.2% vs 21.3%).There was no effect of Pre-Diabetes on TB treatment outcome. Conclusion: This converging of two epidemics should be a wakeup call for all clinicians and researchers to gearup to meet the challenge of patients afflicted by tuberculosis as well as diabetes. It is time that the “unhealthy partnership” of tuberculosis and diabetes receives the attention it deserves